ANALISIS HUKUM PERBANKAN TERHADAP PERJANJIAN KREDIT DENGAN JAMINAN SERTIFIKAT PENDIDIKAN GURU PNS - Multahibun Multahibun (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2017)
Credit for banks is the main activity, because the largest income from banks comes from the credit sector that is almost 95% of the sector either in the form of interest, provision, or other income. The amount of credit disbursed will determine the profitability and business continuity of a bank. Therefore, lending should be done well, starting from the planning of the credit, the determination of interest rates, crediting procedures, credit analysis, to the return on credit jams. While the importance of lending activities is a strategic function of the bank and this function is also often the cause bankrutnya a bank. This study aims to find out about: 1) What is the legal basis that allows Decree (SK) Civil Servants can be used as collateral by the debtor to the creditor. 2) How the settlement process will be taken by the creditor (bank) in case of legal conflict (Bad Credit). 3) What is the juridical liability of the banker against customer bad debts. The approach method used in this research is juridical-empirical. The juridical-empirical approach method, which is an approach that examines secondary data first and then proceed with conducting primary data research in the field. Or in other words, this research is carried out by conducting assessment and processing of research data with the starting point on the legal aspects of normative accompanied by theoretical legal studies, supported by empirical facts in the field. The results showed that the PNS Teacher Educator Certificate requirement for civil servant teachers get professional allowance so that teachers can be a legal guarantee in banking law and credit law principles. In the event of a non-performing loan, the bank shall have the right to settle both peacefully and through due process of law. In addition, since PD BPR Astanajapura is a Rural Bank which is a Regional Enterprise (BUMD), then bankers have juridical responsibility for customer bad debts because it is detrimental to the state's wealth. Keywords: Agreement, Credit with Guarantee, Education Certificate, Civil Servant Teacher